INTERNATIONAL HUMAN RESOURCE MANAGEMENT FOR EXPATRIATION IN EARLY AND LATE MOVER MULTINATIONALS - Maciel, Alessandra Costenaro; Mores, Giana de Vargas; Oliva, Eduardo de Camargo; Kubo, Edson Keyso de Miranda (Revista Gestão Organizacional, 2019)
The rise of multinational corporations in emerging economies led to an interest in understanding human resource management in multinationals with subsidiaries. Our research aims to analyze the IHRM practices used for the expatriation of professionals in early and late mover multinationals located in Brazil. This research has a qualitative approach with multiple case studies, and it is both exploratory and descriptive. We perform interviews, document analyses, and observation. The results show similarities between both analyzed groups, except in the recruitment and selection, career development, and work relations practices. We conclude that both in the early and late mover multinationals there are no repatriation programs focused on career development, and a specific process to assess the expatriates’ performance.